ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS XII MATERI APLIKASI TURUNAN FUNGSI TRIGONOMETRI - Dinar Ibrahima; Rasiman Rasiman; Rizky Esti Utami; Ami Ariyani (LPPM Universitas Bina Bangsa, 2024)
Problem solving ability is one of the important goals of learning mathematics, besides that problem-solving ability plays an important role in life. The purpose of this research is to analyze the problem-solving abilities of grade XII students at SMAN 11 Semarang in the application of trigonometric function derivatives. The research method used in this study is the analysis method. The sampling technique used is purposive sampling. The instrument for collecting data in this study is a mathematical problem-solving ability test. All students in grade XII MIPA 3 were identified for their problem-solving abilities with a problem-solving ability test. The test was conducted on the Absolute Value material. Furthermore, the analysis of all data was carried out with the following steps: data reduction stage, data presentation stage, and conclusion. The results of the study show that the problem-solving abilities of students, viewed from the Polya problem-solving steps, are good